2006
DOI: 10.1002/acp.1219
|View full text |Cite
|
Sign up to set email alerts
|

Discussion affects memory for true and false childhood events

Abstract: Although people often reminisce about their past experiences, little research has assessed how discussion might influence people's autobiographical memories. There were two major aims to this study: first, to assess how adults' memories for genuine childhood experiences might be affected by discussion, and second, to extend research on false memories by exploring how memories for false events might be affected by discussion. Siblings attempted to recall four childhood events-three true and one false-three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…We chose the balloon ride because it is a moderately significant and presumably unique event, yet it is available to all New Zealanders (with several balloon festivals and operators throughout the country). Moreover, it has also been used in several previous studies that have been conducted with both American and New Zealand children and adults (Ceci, Huffman, & Smith, & Loftus, 1994;Garry & Wade, 2005;French et al, 2006;Strange, Sutherland, & Garry, 2006;Wade et al, 2002).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…We chose the balloon ride because it is a moderately significant and presumably unique event, yet it is available to all New Zealanders (with several balloon festivals and operators throughout the country). Moreover, it has also been used in several previous studies that have been conducted with both American and New Zealand children and adults (Ceci, Huffman, & Smith, & Loftus, 1994;Garry & Wade, 2005;French et al, 2006;Strange, Sutherland, & Garry, 2006;Wade et al, 2002).…”
Section: Methodsmentioning
confidence: 97%
“…The MQQ is a measure of the quality of a participant's recollection of each event and is made up of four statements adapted from earlier research (French et al, 2006;Wade et al, 2002): (1) ''as I remember the event, I feel as though I am reliving the original event''; (2) ''as I think about the event, I can actually remember it '. These questions were rated on a 7-point Likert scale, where 1 was ''not at all'' and 7 was ''as much as any memory''.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of siblings' memories for shared childhood experiences found that the vast majority (75%) of the details subjects remembered were different from the details their sibling remembered (French, Sutherland, & Garry, 2006). We do not take in everything we see; we rarely remember everything we take in; and we often cannot describe everything we have remembered.…”
mentioning
confidence: 93%
“…Er zijn implantatieonderzoeken die gebruik maken van valse verhaaltjes (French, Sutherland, & Garry, 2006;Mazzoni, Loftus, & Kirsch, 2001;Ost, Foster, Costall, & Bull, 2005;Porter, Yuille, & Lehman, 1999). Grofweg komen deze onderzoeken op het volgende neer.…”
Section: Een Handjevol Onderzoekunclassified